How Do Java Mutation Tools Differ? A framework for aiding future Java mutation tool comparisons. - AMALFITANO, DOMENICO; PAIVA, ANA C. R.; INQUEL, ALEXIS; PINTO, LUÍS; FASOLINO, ANNA RITA; JUST, RENÉ (Communications of the ACM, 2022)
This article presents a system for evaluating Java mutation tools, tools which enable test efficacy and debugging in computer software. The authors compare eight Java mutation tools and provide a framework that can be applied to both current and future mutation tools. The framework provided incorporates five areas of analysis- tool version, deployment, mutation process, user-centric features and mutation operators.